(untitled) (Journal of Parents and Teachers, 2014)
Learning skill is not innate nor spontaneous but essential in this society of information where, more than ever, what Brooks Adams said becomes real: “they know enough who know how to learn”. Form quotes like Adam’s one, the author reflects about this skill development since the early childhood and summarizes in a chart some resources and applications which are on the Internet and that are useful for this goal.